Do Auctions select Efficient Firms? - Maarten C.W. Janssen; Vladimir A. Karamychev (Tinbergen Institute, 2007)
This paper considers a government auctioning off multiple licenses to firms who compete in a market after the auction. Firms have different costs, and cost efficiency is private information at the auction stage and the market competition stage. If only one license is auctioned, standard results say that the most efficient firm wins the auction (license) as it will get the highest profit in the aftermarket, i.e., it has the highest valuation for the license. This paper argues that this result does not generalize to the case of multiple licenses and aftermarket competition. In particular, we determine conditions under which auctions may select inefficient firms and therefore lead to an inefficient allocation of resources. Strategic interactions in the aftermarket, in particular firms' preferences to compete with the least cost-efficient firms rather than with the most efficient firms, are responsible for our result.
Keywords: D43; L11; L13; 330; Auctions; cost-efficiency; aftermarkets; Auktion; Technische Effizienz; Allokationseffizienz; Unvollkommener Markt; Theorie